Evaluasi Pelaksanaan Asesmen Kompetensi Minimum (AKM) Pada Kompetensi Dasar Literasi Sains Siswa Sekolah Dasar - Rizky Rahmad Widiyanto; Anatri Desstya (Universitas Negeri Padang, 2023)
This research intended to evaluate the implementation of AKM at Petunjungan 01 Public Elementary School in Brebes city. This is qualitative research with the CIPP model, including context, input, process, and product in the implementation of AKM. Data collection was done through documentation and interviews with 5th-grade teacher and proctor. The data analysis technique used three procedures: data reduction, data presentation, and conclusion. The results of this study: aspect of context, the implementation of AKM is carried out to improve science literacy in the era of technological change. Aspect of input, the school provides special AKM training using AKM exercise books on literacy and numeracy questions. Aspect of the AKM implementation process, Petunjungan 01 Public Elementary School conducted the AKM on November 2-3, 2022, using the online mode and divided into 3 sessions. Aspect of products, the results of the AKM have not yet been received by the school, but during the teaching and learning process, student's abilities, especially science literacy, have improved. A thorough and accurate evaluation of the implementation of AKM is expected to improve the implementation of AKM in the following year so that the results obtained will be maximized.